Alphakids: farmyard friends - Oldfield, Sara; Tonkin, Ross (Horwitz Education St. Leonards, N.S.W., 2004)
"Farmyard Friends" is a charming children's book that introduces young readers to the delightful animals found on a farm. Through lively illustrations and engaging rhymes, the story highlights various farm animals, such as cows, pigs, sheep, and chickens, showcasing their unique characteristics and sounds. As the narrative unfolds, children learn about the roles each animal plays on the farm and the importance of caring for them. The book fosters a sense of connection to nature and encourages curiosity about rural life, all while celebrating the joy and friendship among farmyard animals.